Characteristics of Metformin Transporter Coding Gene (SLC22A1 rs628031 and SLC47A1 rs2289669) in Healthy Indonesian Subject: Karakteristik Gen Penyandi Transporter Metformin (SLC22A1 rs628031 dan SLC47A1 rs2289669) pada Subyek Sehat Orang Indonesia - Susilowati, Endang (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2024)
Background: Metformin might be a first therapy for Type 2 diabetes; however, it had a lot of variation in glycemic response. Objective: to analyze the frequency of minor alleles of the OCT1 coding gene (SLC22A1 rs628031) and MATE1 coding gene (SLC47A1 rs2289669) as well as the genotypic variation of the interaction of these two genetic polymorphisms in healthy subjects of Indonesia. Material and Methods: Through inclusion criteria, the study employed an observational descriptive technique with 70 Indonesian Javanese healthy individuals. Subject health information was obtained from the complete blood routine test, serum glutamic oxaloacetic transaminase/ serum glutamic-pyruvic transaminase (SGOT/SGPT), complete urine test, and serum creatinine tests. All data were compared to the normal range. Results: The finding shows that the minor allele frequency on SLC22A1 rs628031 A>G and SLC47A1 rs2289669 G>A respectively at 53% and 36%. There are four SLC22A1 rs628031 and SLC47A1 rs2289669 genetic polymorphism interactions; 16 Wt/Wt (16.75%), 24 Wt/M (25%), 32 M/Wt (33.3%) and 24 M/M (25%). The discovery demonstrates that such minor allele frequencies of the SLC22A1 rs628031 OCT1 and SLC47A1 rs2289669 MATE1 genes in healthy Indonesian subjects are relatively high. The SLC22A1 rs628031 A>G and SLC47A1 rs2289669 G>A respectively at 53% and 36%, almost the same as the minor allele frequencies found in several other Asian countries eg. India, Japan, and China. Conclusions: OCT1 coding genes (SLC22A1 rs628031 A>G) were found more dominant than MATE1 coding genes (SLC47A1 rs2289669 G>A) and both alleles are relatively high in healthy subjects of Indonesia, which can be used as information to explore the consequences of different genes' interactions on the Indonesian pharmacokinetic properties, and the efficacy variations of metformin in Type2 DM patients.